ANALYSIS OF THE RECEPTIONIST SERVICE QUALITY ON GUEST SATISFACTION AT HARPER KUTA HOTEL - Anak Agung Kompiang Trijaya Putra; Ni Nyoman Sri Astuti; Ni Ketut Bagiastuti (Politeknik Negeri Bali, 2020)
This research is based on the importance of the role of the receptionist as a brand image of a hotel in terms of first impressions and final impressions for guests who stay overnight. Services provided to guests are expected to be able to meet expectations or even exceed them. This research is intended to measure and analyze the quality of receptionist services to guest satisfaction at Harper Kuta Hotel, using servqual method to check the gap both partially, simultaneously. By using servqual which is used as 16 indicators X, against the Overall of Guest Satisfaction, Customer Loyalty. The average expectation of respondents is 3.60 while the average perception is 3.52. Respondents were determined by random sampling method and with the method of determining the number of samples using the Slovin method, the number of respondents was 99 respondents. The data analysis technique used is validity test, reliability test, servqual method and data processing using SPSS 25 software to analyze multiple linear regression. Based on the results of data processing obtained 3 positive indicators, namely the infrastructure supporting the receptionist is adequate, the receptionist provides services professionally, the receptionist provides general information correctly and updates. While other variables produce negative gaps that have an adverse effect.